VACCINE COVID-19: REFUSAL TREATMENT IN INDONESIA - Firdaus, Sunny Ummul; Wiwoho, Jamal; Hidayat, Muhamad Alief (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
This study investigated the problem of COVID-19 vaccination program refusal. To solve this problem, it is necessary to develop regulations governing sanctions for the COVID-19 vaccination program refusal and include the sanctions on informed consent documents. An informed consent document can be the basis for health workers to give a person a COVID-19 vaccine and can be concrete evidence that a person refuses to be vaccinated. This is very important considering that the COVID-19 vaccination program is expected to be able to accelerate COVID-19 handling and prevention by achieving herd immunity. In this study, the researchers applied a socio-legal research method. This study investigated several things. The first is the problem of the COVID-19 vaccination program refusal. The second is a legal perspective on the COVID-19 vaccination program refusal. The third is a recommended regulation model to deal with the problem of COVID-19 vaccination program refusal.